1999
DOI: 10.1128/jcm.37.12.4028-4033.1999
|View full text |Cite
|
Sign up to set email alerts
|

Porphyromonas gingivalis Strain Variability and Periodontitis

Abstract: To determine if there is variability in virulence among strains ofPorphyromonas gingivalis in human periodontitis, their distribution in a group of subjects with clear indicators of periodontitis and in a healthy, age-matched control group was examined. The presence of heteroduplex types of P. gingivalis in the two groups was determined with a PCR-based assay. This assay relied on detection of polymorphisms in the ribosomal internal spacer region (ISR). ISR fragments generated by PCR with P. gingivalis-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
60
1
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(69 citation statements)
references
References 34 publications
2
60
1
5
Order By: Relevance
“…Besides genotype II ¢mbrillin expression, certain heteroduplex types of the ribosomal intergenic spacer region have been linked to human periodontitis [23]. Strains with close relationship to W83^a reference strain for ¢mA genotype IV^were found to be signi¢cantly associated with chronic periodontitis, whereas strains that grouped with A7A1, a marker strain of ¢mA genotype II, showed no disease association because of their frequent presence at healthy sites [23].…”
Section: Discussionmentioning
confidence: 99%
“…Besides genotype II ¢mbrillin expression, certain heteroduplex types of the ribosomal intergenic spacer region have been linked to human periodontitis [23]. Strains with close relationship to W83^a reference strain for ¢mA genotype IV^were found to be signi¢cantly associated with chronic periodontitis, whereas strains that grouped with A7A1, a marker strain of ¢mA genotype II, showed no disease association because of their frequent presence at healthy sites [23].…”
Section: Discussionmentioning
confidence: 99%
“…This strain was selected for the study as it has been shown to be virulent in murine periodontitis models [90][91][92] and because W50/W83-like strains, based on polymorphisms in the ribosomal internal spacer region, have been closely associated with periodontitis in humans. 93 P. gingivalis W50 was grown and harvested as described previously. [94][95][96] Preparation of heat-killed P. gingivalis W50 (HK-W50) and purification of the RgpA-Kgp proteinase-adhesin complexes (RgpA-Kgp complexes)…”
Section: Animal Ethicsmentioning
confidence: 99%
“…Although the current assumption suggests that a host-dependent exaggerated pro-inflammatory response is the main reason for periodontal destruction, it is possible that different bacterial strains may induce different levels of response. In order to test this possibility, investigators used different strains of P. gingi-valis in various animal models, such as the mouse skin abscess model (Grenier & Mayrand 1987, Ebersole et al 1995b, Griffen et al 1999, the subcutaneous chamber model (Genco et al 1991, Genco & Arko 1994 and the oral infection model (Evans et al 1992, Baker et al 2000. In these studies, many strains of P. gingivalis were classified as either virulent or avirulent; however, the correlation between alveolar bone loss (ABL) and the host immune response following infection with different P. gingivalis strains needs further clarification.…”
mentioning
confidence: 99%